When Qualitative Research is Taught Virtually: Drawing on Experiential Design to Build Deeper Knowledge of Qualitative Observation - Joy C. Phillips; Kristine S. Lewis Grant; Kathy D. Geller (Impacting Education, 2021)
This essay discusses the EdD Program design and qualitative research course sequence at Drexel University, a private, non-profit institution. This large program admits up to 140 EdD students annually with approximately 100 attending fully online and 40 attending hybrid offerings at the main campus and at a satellite program in Washington, DC. The essay features a qualitative course observation activity designed by Janesick (2011) to be used face-to-face and details how the activity has been adapted for virtual delivery at East Coast University. As a literature review revealed a paucity of published works on teaching observation qualitatively, the authors seek to contribute to the knowledge base with particular emphasis on faculty teaching in an online program. Based upon the East Coast University faculty’s use of this observation activity, students develop increased understanding of the roles of perception and perspective in qualitative observation.